Questioning the Sanctity of 'Inclusiveness' of Constitution in Making Process: Reading Dissents and Demands in Nepal (Sambahak: Human Rights Journal, 2025)
The term "inclusion" is mystically undefined in any articulation of the Constitution of Nepal. This leads to two key assumptions: first, the concept of inclusion must be understood and practiced in alignment with its purpose; and second, it encompasses a broader scope and meaning. The constitution-making process is generally assumed to have incorporated the basic requirements of inclusion, as prescribed in constitutional law literature. Inclusion must be studied through the lens of exclusion, and it should be defined and acknowledged in light of historical grievances, supported by evidence and records of state neglect. This research follows the doctrinal method and is based on primary sources of authority. Nepal’s constitution-making process has been often leading to the extreme proposition that exclusion can only be addressed through constitutional means and that inclusion is the ultimate remedy for all grievances. It is crucial to consider dissent in the constitution-making process when addressing public demands, as seen in Nepal. This paper is based on three central propositions for analyzing narratives of inclusiveness in the constitution-making process: first, whether the Nepalese constitution is inclusive in nature or character; second, to what extent inclusiveness has been addressed in the constitution; and third, what the perceptions of lawmakers and constitutional experts are regarding its inclusivity.